Python Django web development : to-do app - Elder, John ([Place of publication not identified] : Packt Publishing, 2019)
"Django and Python may seem challenging at first, but with the right guidance, you can gain the confidence to work with them effectively. In this course, you'll learn through a step-by-step manner, quickly and easily, and also be able to create professional looking websites, even if you have no programming or web design experience. You'll watch and learn as the instructor demonstrates how to build a cool to-do list app. You can follow the instructions and even build your own version of the app. After building the web app, you can make lists and even save them to a database. You can then update the list as you complete the tasks by crossing them off the list. The course will also help you focus on styling the website using the popular Bootstrap CSS framework. By the end of this course, you'll have a strong understanding of Django and the skills to use it for building interactive web apps."--Resource description page
Presenter, John Elder.
Title from resource description page (Safari, viewed March 4, 2020).
In English.
Keywords: Django (Electronic resource); Django (Electronic resource); Python (Computer program language); Application software -- Development; Web applications; Python (Langage de programmation); Logiciels d'application -- Développement.; Applications Web; Application software -- Development; Python (Computer program language); Web applications; Instructional films; Instructional films; Films de formation